KAUSALITAS PERTUMBUHAN EKONOMI KEPADATAN PENDUDUK DAN KEMISKINAN DI PROVINSI ACEH - Fahmi Aqsal; Raja Masbar (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2023)
AbstrackThis research consists in in Aceh Province of the variables of economic growth, population density, and poverty, the data used is in the form of annual time series data, namely 2000-2021, which comes from the Aceh Central Statistics Agency (BPS). This study uses descriptive and quantitative methods with the data analysis technique Vector Error Correction Model (VECM) which is in line with the problem formulation and research objectives. The results of the research show that in the short term, the variables of economic growth and population density together harm poverty. Then the variables of poverty and population density together harm economic growth in the short term. Meanwhile, the variables of poverty and economic growth individually have opposite effects in the long run. This explains that these three variables are important factors in the economy. It is hoped that the government will be able to create accelerated economic growth to offset the growth in population density so that it can significantly reduce the poverty rate.Keywords: Economic Growth, Population Density, Poverty